Digital evidence and its use for criminal proceedings - Matis, Jakub (Аналітично-порівняльне правознавство, 2025)
This paper examines the role and admissibility of digital evidence, particularly data derived from instant messaging applications like WhatsApp and Telegram, in criminal proceedings within the legal context of the Slovak Republic. The focus is on the legal provisions and frameworks under the Slovak Criminal Procedure Code Act, especially regarding the seizure, preservation, and submission of digital data in criminal proceeding. A key aspect of this study is the exploration of how messages and other data from messaging applications are treated as evidence, addressing the complexities of their relevance, authenticity, and credibility in a legal context. In order to establish the admissibility of such evidence in court, the paper delves into essential principles such as the requirement for evidence to be relevant, authentic, and trustworthy. It highlights the fact that courts generally require clear authentication procedures to confirm the authorship of messages, which presents challenges due to the nature of online identities and the potential for manipulation or misrepresentation. The use of screenshots and the specific criteria that ensure they maintain evidentiary value are also discussed, reflecting the practical considerations involved in collecting and presenting digital evidence. Additionally, the paper critiques existing legal provisions in the Slovak Criminal Procedure Code, particularly those that address the seizure and handling of digital data stored on mobile devices and computers. There are notable ambiguities regarding the categorization of mobile devices as computers and the applicable procedures for accessing data from them. The study argues that the current legal framework should be amended to include a clear definition of digital evidence, to standardize the procedures for its collection, preservation, and presentation in court, and to resolve the conflicting interpretations that currently exist in practice. By examining these aspects, the paper contributes to a deeper understanding of how digital evidence is utilized in criminal investigations and legal proceedings, advocating for legislative updates to address the growing importance of digital data in modern criminal cases. Furthermore, it underscores the need for careful consideration of privacy rights and proportionality when dealing with personal information obtained from digital devices and online platforms.